Audit IT Gov Dan IT Process Investasi Simperang Menggunakan Framework Cobit 4.0 Pada Politeknik Negeri Bandung - Agung Gunawan; Rendra Trisyanto Surya (Indonesian Accounting Literacy Journal, 2021)
Technology advances that are increasingly rapid affect the nature and structure of the organization's operational system, one form of change is the existence of a budget planning system (SIMPERANG). The use of technology-based information systems like this needs to be done in analysing the IT Risk Management contained in the system, as well as to measure the maturity level of Information Technology and Investment Management. The audit was carried out using a framework that became an international standard namely COBIT 4.1 which provides information on size, indicators, processes, and a collection of best practices to help the organization be optimal in managing Information Technology and develop controls on SIMPERANG. Maturity level measurement is based on four domains in COBIT, namely Planning and Organizing (PO), Acquire and Implementation (AI), Delivery and Support (DS), and Monitor and Evaluate (ME). The results of research conducted at SIMPERANG, obtained a maturity level of 2,93 or are at level 2, which is "Repeatable but Intuitive". The results of this audit process and recommendations made are expected to be a reference in the development and improvement of SIMPERANG in order to optimize the effectiveness and efficiency of SIMPERANG in the future at the Bandung State Polytechnic.